2015
DOI: 10.1016/j.medici.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The cost of newly diagnosed breast cancer in Lithuania, 2011

Abstract: The direct BC medical cost estimates provided by this analysis can be used to determine priorities for the future research on BC treatment interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
4
5
1
Order By: Relevance
“…Consistent with other studies [24][25][26][27], the medication costs accounted for the major portion of total costs, due to the high price of new chemotherapeutic agents. On the other hand, the price of services in Jordan and other developing countries was relatively low compared with developed countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with other studies [24][25][26][27], the medication costs accounted for the major portion of total costs, due to the high price of new chemotherapeutic agents. On the other hand, the price of services in Jordan and other developing countries was relatively low compared with developed countries.…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to the findings of Barron's et al [30], where laboratory cost stands as the second highest cost driver after hospitalization. However, in other studies, laboratory test costs were minimal compared with other healthcare resources spent [25,26]. Hospitalization cost (i.e., hospital stay cost) was found to be the third highest cost driver in this study, representing 6.7% of the total direct medical cost.…”
Section: Discussionmentioning
confidence: 50%
“…Our study also showed that hospitalization costs, albeit consistently lower than medication costs, increased as the disease progressed. This finding is, however, inconsistent with other studies that reported higher hospitalization costs for breast cancer patients; this may be ascribed to differences in the healthcare systems, patient populations, and treatment protocols evaluated [ 35 , 36 ]. Assessing the impact of decreased hospitalization costs on overall cost and quality of life, compared to that reported in other countries, would be an interesting topic for future investigation.…”
Section: Discussioncontrasting
confidence: 92%
“…The economic aspects of BC have been subject to growing awareness in health services research and most studies focused on costs of the disease. The studies estimating direct costs conducted in the United States [ 7 11 ], Germany [ 12 ], Poland [ 6 , 13 ] and Lithuania [ 14 ] provide evidence on the magnitude of costs associated with BC treatment while the research focusing on indirect costs estimate productivity losses in Spain [ 15 ] and Lithuania [ 16 ]. Recently, there has been a growing interest in research combining direct and indirect costs within the cost-of-illness framework [ 17 ] as examples from Iran [ 18 ], Korea [ 19 ], Flanders [ 20 ], Sweden [ 21 ], Japan [ 22 ] and California [ 23 ] show.…”
Section: Introductionmentioning
confidence: 99%